Treatment strategies for endometrial cancer: current practice and perspective. Issue 1 (February 2017) - Lee, Yeh C.; Lheureux, Stephanie; Oza, Amit M.
Abstract : Purpose of review: Endometrial cancer incidence is increasing in North America and is a major cause of morbidity and mortality in women. We review recent literature published on treatment of endometrial cancer and highlight areas of active interest. Recent findings: There has been movement toward minimal invasive surgery at diagnosis; lymph node staging remains controversial and continues to be investigated. Progress has been made to establish consensus on endometrial cancer risk classification to promote consistency for future trial design. Molecular characterization of endometrial cancer and its integration into clinicopathological profiling to develop predictive biomarkers for treatment selection are active areas of research. Optimal adjuvant treatment strategy in high-risk endometrial cancer remains to be defined with recognition of treatment-related toxicity. Despite encouraging results in drug development for treatment of advanced/recurrent endometrial cancer, no targeted therapies beyond hormonal therapy are approved. There is an urgent need for scientifically validated therapy with predictive biomarkers. Summary: Our understanding of endometrial cancer has evolved through improvements in molecular biology, allowing improved definition of target-specific therapies. The precise role and sequence of conventional and targeted therapies, including immunotherapy, will require careful attention to the design of clinical trials with translational emphasis to allow the discovery, validation, and implementation of predictive biomarkers into clinical care.